2017
DOI: 10.1101/200154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WDR11-mediated Hedgehog signalling defects underlie a new ciliopathy related to Kallmann syndrome

Abstract: WDR11 has been implicated in congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome (KS), human developmental genetic disorders defined by delayed puberty and infertility. However, WDR11's role in development is poorly understood. Here we report that WDR11 modulates the Hedgehog (Hh) signalling pathway and is essential for ciliogenesis. Disruption of WDR11 expression in mouse and zebrafish results in phenotypic characteristics associated with defective Hh signalling, accompanied by dysgenesis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Similarly, variations in the WDR11 gene have been associated with ciliopathy-related disorders and Kallmann syndrome. Associated features include pituitary dysgenesis and obesity [Kim et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, variations in the WDR11 gene have been associated with ciliopathy-related disorders and Kallmann syndrome. Associated features include pituitary dysgenesis and obesity [Kim et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Slides were incubated for 24 hours in primary antibodies in a humid chamber. The following antibodies and concentrations were used: mouse-YAP (1:100, Santa Cruz, #101199, (Szymaniak et al, 2017;Zanconato et al, 2015)), rabbit-pYAP (1:500, Cell Signaling, #4911, (Heallen et al, 2013)), rabbit-SOX9 (1:500, Millipore, AB5535, (Poché et al, 2008)), mouse-TEAD1 (1:1000, BD transduction, 610923, (Cao et al, 2008)), mouse-SOX2 (1:500, Santa Cruz, 365823, (Xiao et al, 2018a)), rabbit-GFAP (1:1000, Dako, Z0334, (Poché et al, 2016)), rabbit-PH3 (1:500, Millipore, 06-570) (Barrasso et al, 2018), rabbit-Ki67 (1:500, Abcam 15580, (Poché et al, 2016)), rabbit-Cyclin D1 (1:1000, Thermo Fisher, 9104, (Poché et al, 2016)), mouse-Cyclin D3 (1:200, Abcam, 28283, ), rabbit-GFP (1:500, Rockland, 600-401-215, (Kovalchuk et al, 2015)), mouse-Flag (1:250, Sigma, F1804, (Zanconato et al, 2015)), chick-beta-Gal (1:500, Abcam, 936, (Kim et al, 2018)), mouse-GS (1:500, Chemicon, MAB302, (Rueda et al, 2016)), mouse-HuC/D (1:100, Invitrogen, A-21271, (Jorstad et al, 2017;Ueki et al, 2015)).…”
Section: Methods Detailsmentioning
confidence: 99%
“…The primary cilium has emerged as an important organelle that controls signal transduction during development and tissue homeostasis. Both, short or abnormally elongated cilia have been reported in patients with ciliopathies and contribute to dysfunctional signalling, highlighting the importance of understanding cilia length regulation (Kim et al , 2018; Oh & Katsanis, 2013; Ramsbottom et al , 2018; Baala et al , 2007; Aguilar et al , 2012). Whereas the majority of studies were so far dedicated to the analysis of cilia assembly and disassembly, little is known about how cilia length is maintained at steady-state.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, relatively long cilia are reported in neurons (8-10µm), whilst much shorter cilia are present in chondrocytes (2µm) (Wann & Knight, 2012; Miyoshi et al , 2014). Variations in the physiological length of cilia causing shortening or over-elongation are reported in ciliopathies, indicated that keeping proper cilia length in each tissue is vital for their signalling function (Guen et al , 2016; Ramsbottom et al , 2018; Leightner et al , 2013; May-Simera et al , 2018; Reiter & Leroux, 2017; Kim et al , 2018).…”
Section: Introductionmentioning
confidence: 99%